KOMUNIKASI PEMASARAN DALAM MEMPROMOSIKAN ANDALUS WISATA KELUARGA DI KECAMATAN KUOK KABUPATEN KAMPAR - Rizki Hervand Putra; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Andalus Family Tourism is an artificial tourist attraction located in Silam Village, Kuok District, Kampar Regency. Increasing the number of visitors requires effective marketing communications to create attractiveness. The manager of the Family Tourism Andalus has integrated a marketing communication component to communicate promotional messages but based on the author's observation data for the last three years, namely 2017 to 2019 the number of visitors has fluctuated. The purpose of this study was to determine the application of marketing communication, social media marketing, sales promotion, electronic word of mouth and events conducted by Andalus Family Tourism.               This study used qualitative research methods. The subjects in the study consisted of ten people, namely managers, employees, and visitors of the Andalus Family Tour who were selected through the snowball technique and accidental technique. Data collection techniques are grouped into three parts, namely observation, interviews and documentation. The data analysis technique used was the interactive data model of Miles and Huberman. Data validity checking used participation extension techniques and triangulation            The results showed that the segmentation of Andalus Family Tourism is the upper middle class, ranging from 2 years to 60 years of age. Andalus Target Family Tourism as many as 2,000 visitors every month. Positioning Andalus Family Tourism is a family tour with friendly services with the theme of sunnah sports, education and entertainment in Kampar Regency. The social media marketing carried out by Andalus Wisata Keluarga is to create social media accounts, namely Instagram, Facebook fanpages, YouTube channels, blogs. The social media accounts created are used to upload photos and videos that aim to inform the public about vehicle information, ticket prices, testimonials and contact persons. Sales promotions that have been carried out by Andalus Family Tourism are promotions at the point of sale, coupons, premiums (gifts), samples, price pack deals, contests and prize draws (content and sweeptakes). The presence of testimonials from visitors in the form of photos or videos on Instagram @andaluswisatakel Keluarga and tags from visitors is an electronic word of mouth that can help convince potential visitors and can disseminate information about Andalus Family Tourism. Andalus Wisata Keluarga seeks to promote existing rides by organizing sport events, events business, personal events and event organizational.